Properties of Pomegranate and Prospects for Its Growth - Turdaliev Avazbek Turdalievich; Mamajonov Gaybullo Gayratjonogli (Research Parks Publishing LLC, 2021)
This article describes the properties of ornamental plant pomegranate, as a subtropical fruit. prospects, resources and favorable climatic conditions in the countries where it grows and the role of pomegranate in the development of agriculture